Relationship of Hemoglobin type with the reproductive performance in Holstein cows for selection - Ahmed, Jaafer R.; Abdullkareem, Talal A.; Kadhum, Abid J. (Journal of Kerbala for Agricultural Sciences, 2016)
This study was undertaken to investigate the relationship of hemoglobin type with the reproductive performance in Holstein cows for selection purposes. This study was executed at the Dairy Cattle Farm and Physiology Laboratory pertaining to the College of Agriculture, University of Baghdad, as well as in private molecular genetics laboratories during the period from 1/11/2013 to 1/11/2014. Blood samples were collected from 40 Holstein cows, and the hemoglobin types were identified using electrophoresis technique. Records were obtained for cow's reproductive performance and their birth death data until weaning. The effect of hemoglobin type on service per conception, interval between calving and subsequent successful mating and non-return rate to estrus was significant (P≤0.05), being all better in AB type. Greater (P≤0.01) variation was noticed in calving interval trait among the cows, being shorter in AB type. On the other hand, higher and lesser (P≤0.05) calves death rates at calving (2.95 ± 0.04 and 1.37 ± 0.04% respectively) were detected in those with B and A types respectively. Moreover, death rates at calving to weaning interval were also influenced by hemoglobin types, being higher (P≤0.05) in B type (9.82 ± 0.07%), along with non-significant differences detected between A (4.69 ± 0.07%) and AB (5.08 ± 0.04%) types. In conclusion, the hemoglobin type can be adopted type of hemoglobin can adopted as selection tool to improve the reproductive performance of Holstein cows, through selecting those with AB type to maximize the economic gain of their breeding projects.